Prognostic role of preoperative carcinoembryonic antigen level in part-solid lung adenocarcinoma. (May 2022) - Yamanashi, Keiji; Hamaji, Masatsugu; Murakami, Kotaro; Shimada, Yoshihisa; Kayawake, Hidenao; Yutaka, Yojiro; Kawaguchi, Yohei; Kudo, Yujin; Ikeda, Norihiko; Date, Hiroshi
Background: Part-solid lung adenocarcinoma appears as a heterogeneous subgroup, and its surgical management is controversial. This study aimed to elucidate whether preoperative carcinoembryonic antigen, a time-honored tumor marker, can be used as a prognostic factor that contributes to its management. Methods: We retrospectively reviewed consecutive patients with clinical-T1a-cN0M0 part-solid adenocarcinoma who underwent surgical resection between January 2011 and December 2015 at two institutions. Results: Overall, 288 patients were identified. The median age was 69 years with 176 patients (61%) being female. The median follow-up time was 5.6 years. Lymph node metastases were found in 6 (15%) of 41 patients with elevated carcinoembryonic antigen levels, while 10 (4.0%) of 247 patients had normal carcinoembryonic antigen levels ( P  = 0.016). The 5-year overall survival rates in patients with normal and elevated carcinoembryonic antigen levels were 96.9% and 87.2%, respectively ( P  = 0.006), and the 5-year relapse-free survival rates were 91.8% and 62.8%, respectively ( P  < 0.001). The multivariable analysis revealed that preoperative carcinoembryonic antigen level was a significant prognostic factor for relapse-free survival (hazard ratio [HR] = 2.92, 95% confidence interval [CI] = 1.63–5.25, P  < 0.001). Among the patients with elevated carcinoembryonic antigen levels, the 5-year overall survival rates in those undergoing lobar resection and segmentectomy were 87.0% and 88.9%, respectively ( P  = 0.59), and the 5-year relapse-free survival rates were 61.7% and 66.7%, respectively ( P  = 0.84). Conclusions: Our data suggest that preoperative carcinoembryonic antigen level appears to be an important predictor of postoperative survival outcomes in early-stage part-solid adenocarcinoma. Further studies are required to optimize management of patients with elevated preoperative carcinoembryonic antigen levels, although segmentectomy appeared acceptable in those patients.